The Consciousness in Dreams, Film, and Architecture - Junaid, Mahreen (European Journal of Multidisciplinary Studies, 2022)
Dreams are a universal phenomenon and tie all mankind together. They have inspired man throughout history from influencing religious mythologies to various scientific innovations. Dreams have also inspired various art works. They are the ultimate visual, spatial and temporal experience and, due to this attribute, dreams are identified with the act of watching movies. Likewise, architecture provides visual, spatial and temporal experience. There are striking similarities between the medium of films and dreams experience. Thus movies have produced the most satisfying imitations of Dream experiences. But even though the architecture also provides a visual, spatial, and temporal experience, the attempt to portray dream characteristics deliberately is rare to find. This paper aims to narrow the gap regarding the understanding of the state of consciousness while experiencing dreams, films, and architecture. Thus, narrowing the gap between the three disciplines. The study is primarily based on qualitative data analysis. The research makes use of discoveries in the field of neuroscience and elaborates on the existing findings. The research concludes that all three disciplines have a lot in common and certain attributes of each can be experienced in the other.